Analisis Isu Perempuan Dalam Konten Dakwah Akun Tiktok Kadam Sidik - dani, Rahma; nasrullah, nasrullah (IAIN Padangsidimpuan, 2024)
This study is interesting to study because the issues raised by Kadam Sidik are about various issues about women. This research uses a qualitative approach. Qualitative research is research that aims to understand what events are experienced by research actors such as behavior, perceptions, and motivation by describing in written form in a natural context using various methods. The object studied in this research is the content of Kadam sidik which discusses women's issues in general or women's issues due to various phenomena that have occurred recently. Related to what women's issues Kadam discusses and what is the da'wah message of Kadam sidik content related to these women's issues? The results of this study are that some of the content related to women's issues speaks a lot about how a woman should be respected in all aspects. Like in the household as a wife and mother and in general. Women should also not always be blamed for the problem of sexual harassment and rape, but even so, women who wear the hijab should try to perfect their hijab according to Sharia law. Kadam also conveyed a message to men to always reduce and control their lusts, not like animals that have no control over themselves. Men should also not feel that they are the most powerful so that they can control their lusts.